Factors Influencing Staff Loyalty to Organization from the Viewpoints of Employees and managers in Rafsanjan University of Medical Sciences - Hamed Zeinali; Afsane Mirzayi; Elnaz Purkhalui (Kerman University of Medical Sciences, 2019)
Factors Influencing Staff Loyalty to Organization from the Viewpoints of Employees and managers in Rafsanjan University of Medical Sciences   Hamed Zeinali1*, Afsane Mirzayi2, Elnaz Purkhalui2   1. PhD of Public Administration, Central Organization of Vali-e-Asr University of Rafsanjan, Rafsanjan, Iran 2. MSc of Public Administration, Department of Public Administration, School of Management, Islamic Azad University, Rafsanjan Branch, Rafsanjan, Iran *Correspondence: 22 Bahman Squire, Vali-e-Asr University, Rafsanjan, Iran Tel: 009834257247                                                  Email: zeinali59@gmail.com Abstract: Background & Objectives: One of the most important factors for the maintenance and improvement of each organization is its employees' loyalty to the organization. The aim of this study was to determine the factors affecting employees' loyalty to the organization from the perspective of staff and managers at Rafsanjan University of Medical Sciences. Methods: From the perspective of staff, the coefficient between the variables of employees' loyalty to the organization and the components of organizational commitment, organizational support and condition, financial benefits and independence and autonomy were 0.412 and 0.192, 0.466 and 0.321, respectively, which shows a significant relationship between staff loyalty to the organization and the mentioned components. From the managers' perspective, the coefficients between employees' loyalty to the organization and the components of organizational commitment, organizational support and also job-organizational conditions were 0.261, 0.464 and 0.442, respectively, which indicates a significant relationship between the loyalty of employees and the mentioned components. Results: Among 159 people died, 69% were girls and 31% were boys. The most kind of accidents occurred to them were injury (39.67%), poisoning (20.56%), and falling (15.11%). Accidents range was higher among girls and among 3-4-year-old children. Age, Sex, and season of death did not have any correlation with the kind of accident however there was a significant correlation between accidents occurred amongunder-5-year-old children and their season of death.  Conclusion: Through establishing critical thinking in the organization, employees can directly express their views and criticisms to the managers, so that the perceptual gap between managers and employees will be reduced. This will make employees more loyal to the organization. Keywords: Employee, Loyalty, Managers, University of Medical Sciences   Citation: Zeinali H, Mirzayi A, Purkhalui E. Factors Influencing Staff Loyalty to Organization from the Viewpoints of Employees and managers in Rafsanjan University of Medical Sciences. Journal of Health Based Research 2019; 5(2): 151-64. [In Persian]